Electronic Health Record Architecture: A Systematic Review - Jahanbakhsh, Maryam; Rabiei, Reza; Asadi, Farkhondeh; Moghaddasi, Hamid (Archives of Advances in Biosciences, 2016)
Numerous advantages are derived from the electronic health record (EHR).Though achieving such advantages depends on its architecture, at present no unique understanding of the architecture dimensions and specifications is available. Therefore, the aim of the present study is a systematic review of architecture perception of the electronic health record. The authors searched the literature in Science Direct, Scopus, PubMed and Proudest Databases (2000 to Jun 2015). Data extraction was done by 2 reviewers on content, structure, content/structure relationship, confidentiality and security of the EHR. Subsequent to refining the 87 retrieved studies, 25 studies were finally included in the study. In the studies and paradigms so far proposed for the EHR, a unique comprehensive architecture model from the viewpoint of research criteria has not been investigated and it has been considered only from some dimensions. Hence, we provide a new definition of the EHR architecture.